Comparison of different treatments used for polycystic ovary syndrome - Llamas, Miriam C.; Montejano, Javier Méndez; Vergara, Maritza Del C. Mudarra; Muñoz, Aldhara Z. Cordero; Vargas, María G. Ramírez; Otero, Andrea Lira; Martínez, Luis A. Pineda; Torres, José M. Zepeda; Díaz, Miriam C. Pérez (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Polycystic ovary syndrome (PCOS) is a disease that currently affects many women of reproductive age. In recent years, the incidence of PCOS has increased, affecting 4% of all women worldwide, with a prevalence of 6% in Mexico. PCOS is a condition characterized by different metabolic, reproductive and hormonal disorders such as hyperandrogenism, chronic anovulation, menorrhagia or infertility. Patients commonly develop clinical alterations such as hirsutism, acne and in some cases, they become overweight or obese. Different medications and therapeutic methods from different literatures were evaluated, both pharmacological such as inositol, metformin, resveratrol, simvastatin, dapagliflozin, which showed great improvement, decreasing the levels of hyperandrogenism in patients, as well as non-pharmacological, of which significant improvements were found with a change in lifestyle, such as exercise, ketogenic diet and herbal medications such as chamomile and cinnamon, which showed a positive change in patients. It is important to make a diffusion and early diagnosis of PCOS, since in this way it will be possible to have a timely treatment, which can be individualized according to the characteristics and needs of each patient.